2012
DOI: 10.3109/10428194.2012.701738
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the clinical detection and management of patients and their family members with familial myelodysplastic syndrome/acute leukemia predisposition syndromes

Abstract: As with most genetic cancer predisposition syndromes, inherited susceptibility to myelodysplastic syndrome (MDS) and acute leukemia (AL) is likely to be more common than previously appreciated. As next-generation sequencing technologies become integrated into clinical practice, we anticipate that the number of cases of familial MDS/AL identified will increase. Although the existence of syndromes predisposing to MDS/AL has been known for some time, clinical guidelines for the screening and management of suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 35 publications
1
96
0
5
Order By: Relevance
“…The latency until the transformation is relatively long. It has been reported that an average age at diagnosis is 33 years (up to 76 years) [23]. This trend remains unchanged in recent reports (Fig.…”
Section: Familial Platelet Disorder (Fpd) With Propensity To Myeloid mentioning
confidence: 86%
See 4 more Smart Citations
“…The latency until the transformation is relatively long. It has been reported that an average age at diagnosis is 33 years (up to 76 years) [23]. This trend remains unchanged in recent reports (Fig.…”
Section: Familial Platelet Disorder (Fpd) With Propensity To Myeloid mentioning
confidence: 86%
“…Currently, the guidelines of clinical management for patients and their families with familial MDS/AL predisposition syndromes are proposed [23]. At diagnosis of FPD/ AML, complete blood count (CBC), bone marrow biopsy and aspiration with cytogenetic analysis, and HLA typing of both the patients and their siblings are recommended.…”
Section: Clinical Management For Fpd/amlmentioning
confidence: 99%
See 3 more Smart Citations